2012
DOI: 10.1080/10286020.2012.702757
|View full text |Cite
|
Sign up to set email alerts
|

Puerarin stimulates osteoblasts differentiation and bone formation through estrogen receptor, p38 MAPK, and Wnt/β-catenin pathways

Abstract: Puerarin is an isoflavone extracted from Radix Puerariae, a traditional Chinese herb used to treat many diseases such as osteoporosis. In this study, puerarin was shown to stimulate alkaline phosphatase (ALP) activity, type I collagen (Col I) secretion, and mineralized nodules formation of primary osteoblasts. Whereas the estrogen receptor (ER) antagonist ICI 182780 was able to reduce the increase in ALP activity and Col I secretion induced by puerarin. Furthermore, puerarin was shown to elevate levels of phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 24 publications
0
28
0
1
Order By: Relevance
“…Puerarin ameliorated learning and memory deficits in mice through normalizing the glutamatergic/GABAergic system and causing synaptic structural modifications in the hippocampus 66 . Previous study showed that neuroprotective effect of puerarin was potentially mediated through the inhibition of glutamate-induced activation of mitochondrial-dependent signaling pathway and calmodulin-dependent protein kinase II (CaMKII)-dependent apoptosis signal-regulating kinase 1(ASK-1)/c-Jun N-terminal kinase (JNK)/p38 signaling pathway 67, 68 .…”
Section: Discussionmentioning
confidence: 99%
“…Puerarin ameliorated learning and memory deficits in mice through normalizing the glutamatergic/GABAergic system and causing synaptic structural modifications in the hippocampus 66 . Previous study showed that neuroprotective effect of puerarin was potentially mediated through the inhibition of glutamate-induced activation of mitochondrial-dependent signaling pathway and calmodulin-dependent protein kinase II (CaMKII)-dependent apoptosis signal-regulating kinase 1(ASK-1)/c-Jun N-terminal kinase (JNK)/p38 signaling pathway 67, 68 .…”
Section: Discussionmentioning
confidence: 99%
“…FGF-2 has been reported to accelerate the initial tendon-to-bone remodeling and FGFR-1 plays a multifunctional role in bone formation and callus remodeling. β-catenin widely exists in fibroblasts and osteoblasts, and it plays an important role in regulating the proliferation, differentiation and apoptosis of these cells [32]. The early growth response 1 (EGR1) plays a vital role in the process of tendon formation, healing, as well as repair through the BMP12/Smad1/5/8 signaling pathway [33].…”
Section: Discussionmentioning
confidence: 99%
“…It possesses estrogen-like structure and moderates estrogenic activity. As a famous phytoestrogen, current studies have established that puerarin provides a strong protection against osteoporosis through facilitating osteoblast proliferation and differentiation [9, 10]. Although it acts as an important regulatory factor for cell death, the role of puerarin on osteoblast apoptosis and its underlying mechanism of action are still unclear.…”
Section: Introductionmentioning
confidence: 99%